Molecular cloning, characterization, and gene expression behavior of glucocorticoid and mineralocorticoid receptors from the Chinese alligator (Alligator sinensis). Issue 1 (11th December 2020) - Izaz, Ali; Pan, Tao; Wang, Lin; Zhang, Huabin; Duan, Shulong; Li, En; Yan, Peng; Wu, Xiaobing
Abstract: The Chinese alligator is an endemic crocodilian species in China. We isolated and obtained the glucocorticoid and mineralocorticoid receptor genes coding from the kidney of  Alligator sinensis by nested polymerase chain reaction (PCR) and rapid amplification of cDNA ends (RACE). The glucocorticoid receptor (GR) gene has 2343 base pairs encoding 780 amino acids, while the mineralocorticoid receptor (MR) gene is 2958 bp in length encoding 985 amino acids. Quantitative real‐time PCR was used to detect the distribution of messenger RNA (mRNA) levels. The maximum mRNA expressions were observed in the ovary and kidney, suggesting that these receptors may be involved in basic cellular functions or stress response of alligators. Besides this, RT‐qPCR was performed to analyze the abundance of GR and MR mRNA transcripts in early embryonic development of the Chinese alligator in the kidney, liver, and heart. The mRNA levels of GR and MR at earlier stages in kidney, liver, and heart indicates that they might involve in the transcriptional regulation of early embryos and activate many precise developmental effects in fetal tissues. We also measured the protein expression in the liver embryonic developmental stages and found that the GR and MR proteins were restricted to both the nuclei and cytoplasm. The protein expression levels in the liver at different embryonic developmental stages have extremely prominent differences. Taken together, our results showed the full coding regions of GR and MR, their characteristics, and embryonic developmental mRNA and protein expressions of both genes in A. sinensis . This study could provide the necessary information for further investigating the diverse functions of GR and MR in A. sinensis . Graphical Abstract: This study showed the full coding regions of GR and MR, their characteristics and embryonic developmental mRNA and protein expressions of both genes in Alligator sinensis.